Pengaruh EWOM dan Pemasaran Digital terhadap Keputusan Pembelian melalui Identitas Merek pada Produk Tolak Angin : Keyakinan Konsume Terhadap Merek sebagai Moderasi - Utami, Dewi Tri; Isa, Muzakar (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE INFLUENCE OF EWOM AND DIGITAL MARKETING ON PURCHASING DECISIONS THROUGH BRAND IDENTITY ON TOLAK ANGIN PRODUCTS: CONSUMER CONFIDENCE IN BRANDS AS MODERATIONThis study aims to analyze the influence of digital competence represented through Electronic Word of Mouth (EWOM) and digital marketing on consumer purchasing decisions for Tolak Angin herbal packaged products, with brand identity as a mediating variable and consumer brand belief as a moderating variable. Using a quantitative approach, the study involved 313 respondents who had purchased or intended to purchase Tolak Angin, selected through purposive sampling. Data were analyzed using SmartPLS 4 through outer model testing, inner model testing, and hypothesis testing. The findings show that EWOM and digital marketing have a positive and significant effect on brand identity. A strong brand identity subsequently enhances consumer purchasing decisions, and consumer belief in the brand also shows a positive direct effect on purchasing decisions. However, contrary to the initial hypothesis, consumer brand belief does not significantly moderate the relationship between brand identity and purchasing decisions. This indicates that although brand belief has a direct impact, it is not strong enough to reinforce the effect of brand identity on purchasing behavior. Overall, the results highlight the importance of strengthening digital communication strategies through both EWOM and digital marketing in enhancing the brand identity of Tolak Angin. A strong brand identity remains the key determinant influencing consumer purchasing decisions for this modern herbal product.